The role of educational biography in the development of professional competencies of pedagogy students - Stanisavljević Petrović, Zorica; Sotirov, Iva; Marković, Marija (Norma, 2026)
The aim of this study was to examine how pedagogy students understand the role of their own educational experiences in shaping key competencies for their future professional roles. The research was conducted within a qualitative framework, and data were collected through a written semi-structured interview on a sample of 25 third-year undergraduate students of pedagogy. The collected data were analyzed using thematic analysis.The results indicate that the process of writing an educational biography contributes to the development of self-understanding, that is, self-concept, as it enables students to recognize their own traits, values, and learning patterns, as well as to reinterpret their educational trajectories. In the domain of professional competencies, students identified empathy, patience, communication skills, professional knowledge, and readiness for continuous learning as key elements of their future pedagogical role. These competencies are perceived by the participants as being directly related to their personal experiences and reflection on their own educational development. The findings suggest that the educational biography represents an important reflective tool in higher education for future pedagogues, as it connects experiential learning, self-understanding, and the development of professional competencies. In this way, it contributes to a deeper understanding of the process of professional identity formation during studies.
Keywords: educational experiences; professional development; higher education; reflective learning; self-understanding